Factors influencing dialysis arteriovenous graft survival - Valerianova, Anna; Kudlicka, Jaroslav; Chytilova, Eva; Grauova, Barbora; Krupickova, Zdislava; Malik, Jan (The journal of vascular access, 2017)
PURPOSE: Dysfunction and loss of patency of dialysis arteriovenous grafts (AVGs) are serious causes of morbidity in patients on dialysis. Various risk factors associated with shorter AVG patency have been blamed, but the results of the studies were controversial. The aim of this study was to assess if associated diseases, biochemical markers and other parameters associated with atherosclerosis influence patency of AVGs in a large vascular access centre. METHODS: We conducted a retrospective study that included patients with AVGs patent for at least 3 weeks after creation. We included variables associated with atherosclerosis into the analysis (coronary artery disease, diabetes mellitus, chronic heart failure, arterial hypertension, smoking history and cholesterol and triglyceride levels) and characteristics of the graft (shape, feeding artery).The data was assessed using log-rank (Cox-Mantel) test. The differences were shown using Kaplan-Meier graphs. The observation period was limited to 1000 days after access creation. RESULTS: Overall, 338 patients were included in the study. Significantly higher risk of access failure was associated with presence of coronary artery disease (p = 0.0035). Higher serum cholesterol levels were associated with longer survival of the graft in 1000 days of surveillance (p = 0.04). CONCLUSIONS: Coronary artery disease negatively influences the cumulative patency of vascular access. Higher serum cholesterol levels are associated with lower AVG failure risk over a 1000-day period, which probably corresponds to the worse disease status of the patients with lower cholesterol values.
Keywords: senioři; proporcionální rizikové modely; průchodnost cév; Proportional Hazards Models; senioři nad 80 let; Graft Occlusion, Vascular; Arteriovenous Shunt, Surgical; Retrospective Studies; komorbidita; Time Factors; nemoci koronárních tepen; mladiství; Česká republika; výsledek terapie; nemocnice univerzitní; Kaplan-Meier Estimate; Middle Aged; Renal Dialysis; mužské pohlaví; Vascular Patency; Kaplanův-Meierův odhad; Adult; mladý dospělý; Cholesterol; Adolescent; Czech Republic; Coronary Artery Disease; Aged, 80 and over; Young Adult; dyslipidemie; ženské pohlaví; retrospektivní studie; Humans; biologické markery; Comorbidity; časové faktory; lidé středního věku; Health Status; rizikové faktory; dialýza ledvin; okluze cévního štěpu; Kidney Failure, Chronic; dospělí; zdravotní stav; Biomarkers; chronické selhání ledvin; Female; Aged; Hospitals, University; Risk Factors; arteriovenózní zkrat; Treatment Outcome; Dyslipidemias; lidé; Male; cholesterol